2021
DOI: 10.1002/ajb2.1591
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic signatures of ecological divergence and leapfrog adaptive radiation inEspeletia

Abstract: Evolutionary radiations, defined as events of accelerated species diversification on relatively short timescales (Simões et al., 2016), have often been documented in many high mountain floras, such as the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 110 publications
(219 reference statements)
1
8
0
Order By: Relevance
“…Their high species diversity may be the result of repeated cycles of allopatry driven by Pleistocene climate changes, periodically allowing páramo species to migrate downslope during cold glacial periods, with upslope movement driving isolation during warmer interglacials. This model of 'flickering connectivity' (Flantua et al, 2019) envisages extensive opportunity for secondary contact and interspecific gene flow, and this is now supported by numerous empirical examples (Nevado et al, 2018;Pouchon et al, 2021). This, coupled with the diversity of habitats resulting from the steep ecological clines along mountain slopes, renders hybridization a relatively common occurrence in the Andes.…”
Section: Hybridization In the Neotropical Floramentioning
confidence: 96%
See 1 more Smart Citation
“…Their high species diversity may be the result of repeated cycles of allopatry driven by Pleistocene climate changes, periodically allowing páramo species to migrate downslope during cold glacial periods, with upslope movement driving isolation during warmer interglacials. This model of 'flickering connectivity' (Flantua et al, 2019) envisages extensive opportunity for secondary contact and interspecific gene flow, and this is now supported by numerous empirical examples (Nevado et al, 2018;Pouchon et al, 2021). This, coupled with the diversity of habitats resulting from the steep ecological clines along mountain slopes, renders hybridization a relatively common occurrence in the Andes.…”
Section: Hybridization In the Neotropical Floramentioning
confidence: 96%
“…Species of Espeletiinae are known to have diversified rapidly, within the last c. 2.3 Myr, and show a wide range of growth forms, from herbaceous rosettes to trees (Monasterio & Sarmiento, 1991). Pouchon et al (2018) used plastid, mitochondrial and nuclear data recovered via genome skimming to show that most diversification in Espeletiinae occurred through climate-driven morphological adaptation, allopatry and ecological speciation (Pouchon et al, 2021) and that hybridization was common between sympatric species. Moreover, they suggested that the broad range of morphological variation in the group and the occurrence of species with admixed phenotypes was probably influenced by the sharing of traits through hybridization that may have been catalysed by repeated periods of habitat connectivity.…”
Section: Hybridization In the Neotropical Floramentioning
confidence: 99%
“…The time is obviously ripe to re-address the timing, mechanisms and patterns of parallel adaptation in the afroalpine flora using genomic approaches. Recent genomic studies of the Andean lineages Espeletia and Lupinus show that diversification often has occurred exceptionally fast via ecological speciation during the last glacial cycles of the Pleistocene, and that small-scale ecological divergence may have occurred along multiple niche dimensions (Nevado et al 2018(Nevado et al , 2019Pouchon et al 2020).…”
Section: Parallel Adaptation: Giants Dwarfs and Cushionsmentioning
confidence: 99%
“…Cuatrecasas (1976Cuatrecasas ( , 1995. See Pouchon et al (2021) for details on phylogenomic reconstructions.…”
Section: Taxonomymentioning
confidence: 99%
“…Color shades highlight genera according toCuatrecasas (1976Cuatrecasas ( , 1995. SeePouchon et al (2021) for details on…”
mentioning
confidence: 99%